2017
DOI: 10.1080/07370016.2017.1304146
|View full text |Cite
|
Sign up to set email alerts
|

Schools as Sites for Recruiting Participants and Implementing Research

Abstract: Schoolscan be a valuable resourcefor recruitment of participants for research involving children, adolescents, and parents. Awareness of the benefits and challenges of working with schools canassist researchersin developing effective school partnerships.This articlediscusses theadvantagesof conducting research within the school system as well as the challenges that may also arise.Such challenges include developing key contacts, building relationships, logistical arrangements, and facilitating trust in the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…A growing literature provides strategies for recruiting diverse populations into clinical trials. For example, studies have shown the importance of building relationships and trust [30], including family referrals and community stakeholders [31], person-to-person outreach, presentations in the community, and face-to-face meetings [32]. More recently, studies have evaluated the use of popular social media platforms (e.g., Twitter, Facebook [18,33]) in recruiting vulnerable populations.…”
Section: Focus On Reach From the Very Beginningmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing literature provides strategies for recruiting diverse populations into clinical trials. For example, studies have shown the importance of building relationships and trust [30], including family referrals and community stakeholders [31], person-to-person outreach, presentations in the community, and face-to-face meetings [32]. More recently, studies have evaluated the use of popular social media platforms (e.g., Twitter, Facebook [18,33]) in recruiting vulnerable populations.…”
Section: Focus On Reach From the Very Beginningmentioning
confidence: 99%
“…Given the reality that vulnerable populations tend to be absent from clinical trials, implementation scientists need to examine where the populations from our implementation trials are, where they are served, and who is providing services to them. For example, conducting studies in non-traditional settings, such as faith communities, family resource agencies, barbershops, and community centers, can increase reach because vulnerable populations may not go to traditional healthcare settings due to stigma, mistrust and discrimination [30,[34][35][36][37]. Implementation and health inequity researchers should aspire to conduct studies that mirror the context of vulnerable populations.…”
Section: Focus On Reach From the Very Beginningmentioning
confidence: 99%
“…In this feasibility study, head teachers were approached only once about the study by email; nevertheless, the poor initial response rate highlights that future research conducted in UK secondary schools may face recruitment challenges. The challenges of recruitment and data collection in schools are recognised internationally [50,51] and therefore we believe that the low response rate in our feasibility study is likely related to the general practicalities of accommodating research in schools irrespective of country. Some head teachers indicated that they were not in a position to participate because there was no space left on the school timetable to accommodate the research.…”
Section: Discussionmentioning
confidence: 99%
“…In this feasibility study, head teachers were approached only once about the study by email; nevertheless, the poor initial response rate highlights that future research conducted in UK secondary schools may face recruitment challenges. The challenges of recruitment and data collection in schools are recognised internationally [51,52] and therefore we believe that the low response rate in our feasibility study is likely related to the general practicalities of accommodating research in schools irrespective of country. Some head teachers indicated that they were not in a position to participate because there was no space left on the school timetable to accommodate the research.…”
Section: Discussionmentioning
confidence: 99%